STUDIES ON THE PERFORMANCE OF ’OVATIDE’ - ON BREEDING OF INDIAN MAJOR CARPS - DUTTA, NARESH C.; MISHRA, SIDDHARTHA S.; PRADHAN, PRASENJIT; CHAKARABORTY, SUSANTA K. (Journal of Indian Fisheries Association, 2015)
The paper deals with the experimental studies on breeding of Indian Major Carps- Catla catla (Valenciennes), Labeo rohita (Hamilton), Cirrhinus mrigala (Hamilton), & Labeo calbasu (Hamilton) with the help of ’Ovatide’ which is being used as an alternative inducing agent for commercial seed production. This study has been conducted for six consecutive months (April -September, 2000) in a stone-pitched breeding channels of a farm located at Midnapore District, West Bengal. The doses of ’Ovatide’ (0.5 mllkg of fish weight) remained same for each female species during the entire study period and males were released without any dose. The physicochemical parameters of water during different months were estimated. The latency period and fertilization percentage varied in different months and species. The results confirmed that ’Ovatide’ can be used successfully in a much more cost-effective way for induced breeding of carps, even in rural fish farms with morrumpitched breeding channels. Keywords : Induced breeding, Indian Major Carps, Ovatide